Lactarius subgenus Russularia (Russulaceae) in Southeast Asia: 1. Species with very distant gills - Wisitrassameewong, Komsit; Nuytinck, Jorinde; Hyde, Kevin D; Verbeken, Annemieke (Phytotaxa, 2014)
This article introduces four new species of Lactarius subgenus Russularia from Southeast Asia with descriptions and illustrations of macromorphological and microscopic characters. Lactarius laccarioides and L. sublaccarioides were discovered in Northern Thailand, and L. pasohensis and L. stubbei in Malaysia. These four species share some striking macroscopic features that are unique in the subgenus: distant gills and a very thin-fleshed and deeply striate to sulcate pileus, which gives them the aspect of Laccaria species in the field. Molecular analysis of the ITS gene region shows that these four species are not as closely related within Lactarius subgenus Russularia as their similar appearance in the field would suggest.